Impact of combined ultrasonic and microwave vacuum drying on physicochemical properties and structural characteristics of polysaccharides from shiitake mushrooms (Lentinus edodes) - Yanping Lei; Ye Xu; Peng Meng; Dongkun Tu; Yingting Zhao; Liping Fu; Yuting Tian (Ultrasonics Sonochemistry)
In this study, ultrasonic technology was combined with microwave vacuum drying technology to explore the impacts of different coupling methods (ultrasonic pretreatment and ultrasonic coupled drying) on the structural characterisation and physicochemical properties of shiitake mushroom (Lentinus edodes) polysaccharides at different ultrasonic powers (0, 120 and 280 W), and compared with hot air drying (HAD). The results demonstrated that the monosaccharide composition of Lentinus edodes polysaccharides (LEPs) remained largely unaltered after treatment with various drying methods, although significant disparities in molar content were observed. Air ultrasound combined with microwave vacuum drying (USMVD) at 280 W ultrasound power resulted in LEPs with higher contents of total sugars (8.12 ± 0.13 g/100 g), reducing sugars (10.32 ± 0.3 mg/g) and uric acid (2.23 %) compared to those obtained from the HAD treatment. Furthermore, the combination of US280MVD drying treatment of LEPs exhibited a reduction in molecular weight and an enhancement in shear-thinning ability. The results of the study indicate that USMVD is a promising drying treatment technology.